HOUSEHOLD CONSUMPTION PATTERN UNDER THE CONTEMPORARY OF CRISIS COVID-19 - Haider Kadhim Mahdi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research is concerned with presenting the concepts related to the consumption process, including household consumption patterns. The most important factors affecting these patterns were also explained, which were divided into internal (subjective) factors, and external factors, also between the study of consumption patterns in Iraqi families in the presence of the volume of spending on necessary and luxury consumer goods. As the research revealed an increase in the volume of household consumption spending equivalent to (60%) of the gross domestic product. The research also showed the potential effects of the current crisis on household consumption patterns in the presence of a decrease in the incomes of working individuals as a result of the suspension of most economic activities, in addition to the most important possible means through which the effects of the current crisis can be mitigated.